Neurological mechanism and efficacy of acupuncture for breast cancer-related insomnia: a study protocol for randomized clinical trial - Liu, Lumin; Yin, Ping; Dong, Yiyue; Fan, Qian; Huai, Yisheng; Zhang, Shijie; Lv, Shunyi; Wang, Xueyang; Chen, Yuelai (Frontiers in Neurology, 2023)
Background: Breast cancer survivors (BCSs) are at a higher risk of developing insomnia. The negative effects of cancer-related insomnia (CRI) include depression, anxiety, fatigue, aggressive pain, impaired immune functioning, decreased quality of life, and even increased cancer mortality.Although preliminary progress has been made in the treatment of CRI with acupuncture, the evidence is insufficient and the neurological mechanism underlying the effect of acupuncture is still unclear.The study employs a single-blinded, randomized, controlled trial design. A total of 80 participants will be randomly allocated in a 1:1 ratio to either the treatment group (n=40) or the control group (n=40). The former will receive acupuncture treatment while the later will receive sham acupuncture treatment. Both groups will receive 12 sessions over a 4-week period, with 3 times per week (every other day), and each session will last for 30 minutes. Follow-up assessments will be conducted at weeks 8. The primary outcome will be the treatment response rate. Secondary outcomes